Beyond positivism, behaviorism, and neoinstitutionalism in economics - McCloskey, Deirdre N. (The University of Chicago Press, 2022)
A penetrating analysis from one of the defining voices of contemporary economics. In Beyond Positivism, Behaviorism, and Neoinstitutionalism in Economics, Deirdre Nansen McCloskey zeroes in on the authoritarian cast of recent economics, arguing for a re-focusing on the liberated human. The behaviorist positivism fashionable in the field since the 1930s treats people from the outside. It yielded in Williamson and North a manipulative neo-institutionalism. McCloskey argues that institutions as causes are mainly temporary and intermediate, not ultimate. They are human-made, depending on words, myth, ethics, ideology, history, identity, professionalism, gossip, movies, what your mother taught you. Humans create conversations as they go, in the economy as in the rest of life. In engaging and erudite prose, McCloskey exhibits in detail the scientific failures of neo-institutionalism. She proposes a "humanomics," an economics with the humans left in. Humanomics keeps theory, quantification, experiment, mathematics, econometrics, though insisting on more true rigor than is usual. It adds what can be learned about the economy from history, philosophy, literature, and all the sciences of humans. McCloskey reaffirms the durability of "market-tested innovation" against the imagined imperfections to be corrected by a perfect government. With her trademark zeal and incisive wit, she rebuilds the foundations of economics.